«Only anarchy can give us the opportunity to defeat the Soviet government»: a memorandum by General M. K. Dieterichs to the leadership of the ROVS (1930) - S. V. Smirnov (Омский научный вестник: Серия "Общество. История. Современность")
The article analyzes a memo from the head of the Shanghai branch of the General Military Union, General M. K. Dieterichs, to the leadership of the ROVS, which is practically unknown to domestic researchers. The document is kept in the collections of the Bakhmetyev Archive of Russian and Eastern European History and Culture at Columbia University. The text of the memo shows the discrepancy between the author’s realistic assessment of the international situation in the Far East, the situation in the Far Eastern regions of the USSR, where there was an increase in discontent with the activities of the Soviet government, as well as the state of White emigration in China and the presentation of the prospects of the anti-Soviet movement based on Dieterichs’ belief in the exclusively repressive and spiritually alien Russian people essence of Soviet power and readiness a significant part of the ordinary military emigration to sacrifice in the overthrow of the «Bolshevik yoke». In the end, this discrepancy had a negative impact on the course of the anti-Soviet struggle.